DOES BRAND IMAGE MEDIATE NUTRI-CLAIMS AND PRICE EFFECTS ON GENZ BEVERAGE CHOICE? - Denis Hartanto; Erwin Erwin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study investigates the trend of healthy lifestyle in Generation Z consumers in Makassar and the adjustment the industry does towards the brand. The research studies the effects of Nutrition Claims and Price Perception towards the Purchase Intention of Generation Z consumers towards packaged beverages with Brand Image as a mediating factor. The respondents consists of 198 Generation Z living in Kota Makassar who have bought or consumed packaged beverages within the last three months. The data were collected via a questionnaire using a 5-point Likert Scale. The collected data is then processed using SEM-PLS using the SmartPLS application. The results show Nutritional Claims cannot give a direct effect towards Purchase Intention. In contrast, Price Perception can directly affect Purchase Intention. The core result is Brand Image becoming the main catalyst heavily affecting the effects of both Nutritional Claims and Price Perception on Purchase Intention. And so, Brand Image is signified as an important mediating variable in this research. This research is important as it signals for companies to not only add Nutritional Claim labels but also build a good Brand Image, weakening price resistance and building trust towards the products.